KAJIAN PENGGUNAAN TEPUNG TAPIOKA DARI BERBAGAI VARIETAS UBI KAYU (Manihot esculenta Crantz.) DAN JENIS IKAN TERHADAP SIFAT SENSORIS PEMPEK - Jayanti, Ulpa; Dasir, Dasir; Idealistuti, Idealistuti (Universitas Muhammadiyah Palembang, 2017)
This study uses a Randomized Block Design (RAK) arranged as factorial consisting of two factors: the varieties of cassava and fish with six combinations treatment and repeated three times. The parameters observed in this study is the physical test includes elasticity and Expressible Moisture Content (EMC) test. While the organoleptic test includes the taste, flavour and color using hedonic test. The results of this study showed, the highest elasticity level of pempek found in interaction of V1J1 treatment (mango varieties and snakehead fish) with a value of 522.23 Newton and lowest in interaction of V3J2 treatment (mentik urang and varieties of Parangparang Fish) with a value of 339.91 Newton. The highest water holding capacity of pempek contained in interaction of V1J1 treatment (99.45%) and the lowest in interaction of V3J2treatment (96.80%). A sensory test of the highest level of pempek in treatment V1J1 (mango varieties and snakehead fish) with an average value of 4.00, which means preferred by 20 panelists.